2012
DOI: 10.1002/jbmr.1742
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound of cortical bone in the femoral neck predicts femur strength: Results of a pilot study

Abstract: A significant risk of femoral neck (FN) fracture exists for men and women with an areal bone mineral density (aBMD) higher than the osteoporotic range, as measured with dual-energy X-ray absorptiometry (DXA). Separately measuring the cortical and trabecular FN compartments and combining the results would likely be a critical aspect of enhancing the diagnostic capabilities of a new technique. Because the cortical shell determines a large part of FN strength a novel quantitative ultrasound (QUS) technique that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…It is cylindrically pre-focused in order to concentrate the beam energy in a plane perpendicular to the FN axis, which is placed at the focal distance. A similar setup with a monoelement probe was used previously to measure femurs in vitro [11].…”
Section: Configuration and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It is cylindrically pre-focused in order to concentrate the beam energy in a plane perpendicular to the FN axis, which is placed at the focal distance. A similar setup with a monoelement probe was used previously to measure femurs in vitro [11].…”
Section: Configuration and Modelmentioning
confidence: 99%
“…The interest for these waves was reinforced by the results of a pilot in vitro study [11] which suggested that there is a strong relationship between femur strength and the time-of-flight of the first arriving signal associated with waves traveling circumferentially. Furthermore, it is likely that several modes of circumferential guided waves can be measured in the cortical bone of the FN using multi-emitter and multi-receiver ultrasonic arrays and dedicated signal processing techniques such as the DORT method [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…calcaneus), with a limited clinical effectiveness [16]. In this context, the latest research frontier is represented by the development of an US approach to osteoporosis diagnosis that is applicable on femoral neck [ [7][8][9][10][11][12][13][14][15][16][17][18][19] and/or lumbar spine [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, several novel technologies based on different physical principles targeting the cortical bone have been tested in human studies. Experimental study with the proximal femur through-transmission scanner showed potential to measure propagation parameters of guided waves in the cortical shell of the femoral neck with an ultrasound beam targeted to the bone through a bulk of the surrounding soft tissues [12]. Correlation of ultrasound propagation parameters with BMD in the distal radius was demonstrated by through transition measurements in the forearm at locations containing composition of soft tissues and bone [13].…”
Section: Introductionmentioning
confidence: 99%